Physicochemical characterization of special cassava starches and their application for bio-ethanol production through no-cook technology at very high gravity - Moreno-Alzate, Jhon Larry; Tran, Thierry; Ceballos, Hernan; Nguyen, Chinh-Nghia; Nguyen, Tien Cuong; Zhang, Xiaofei; Newby, Jonathan; Dufour, Dominique; Chu-Ky, Son (Elsevier, 2024)
Various cassava genotypes were developed with distinct starch characteristics, including amylose-free and small-granule mutations. Despite these unique traits, the ethanol production potential of these starches has not been explored. Cassava starch plays a crucial role in ethanol production, particularly in tropical countries like Colombia. This study aimed to assess the physicochemical properties of different cassava starches (including the amylose-free and small granule mutations), and to evaluate their potential for ethanol production using the Simultaneous Liquefaction, Saccharification, and Fermentation process under very high gravity (SLSF-VHG) and no-cooking conditions. Comparative analysis revealed that two double mutant starches and small-granule starch (GM4694–1) exhibited lower resistant starch content than those from wild-type and amylose-free cassava, making them more susceptible to enzymatic breakdown. The amylose content for GM4694–1 and wild-type cassava was 21.9 and 16.1 %, respectively, while the remaining samples were amylose-free. In the SLSF-VHG process, GM4694–1 demonstrated a significant ethanol yield, surpassing 16 % v/v, equivalent to 80 % of the theoretical ethanol yield within 90 hours. This suggests that the GM4694–1 genotype has the potential to produce ethanol efficiently at a temperature of 30°C. Furthermore, the solid residue obtained after the SLSF-VHG process could serve as a high-quality feed additive. This study enhances our understanding of the properties of special cassava starches and their correlation with ethanol production.